THE EFFECT OF SELF EFFICIENCY, WORK ENVIRONMENT AND JOB SATISFACTION ON TEACHER PERFORMANCE AT HIGH SCHOOL IN BANTEN - Nurdin, Ali; Samudi, Samudi (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2022)
This study aims to examine, analyze and formulate the influence of self-efficacy, work environment and job satisfaction on teacher performance. This research was conducted at High School Mathla'ul Anwar Pandeglang Banten. This study uses survey methods and data analysis techniques using regression. The results of this study indicate that partially each independent variable in this study has a positive and significant effect on the dependent variable with a very good influence value. Meanwhile, simultaneously that self-efficacy, work environment and job satisfaction have a positive and significant effect on teacher performance with a very good influence value. Based on this, it can be concluded that self-efficacy, work environment and job satisfaction can make a very good contribution to teacher performance, so it must be a consideration in managing teacher performance in the field of Islamic religious education studies at High School Mathla'ul Anwar Pandeglang Banten.